1972
DOI: 10.1002/crat.19720070108
|View full text |Cite
|
Sign up to set email alerts
|

Nichtstationäre Keimbildung: Theorie und Experiment

Abstract: The present paper reviews some basic problems in the kinetics of nilcleation giving particular attention to the non-st,eady state charachr of this process. The detailed analysis of the mechanism of nucleation makes i t possible to evaluato the influence of active substrates and that of the properties of both the mother and new phases on the magnitude of t.he non-steady state time lag. Some probabilistic aspects of homogeneous and hcterogencous nucleation as well as thc impact, of non-stat,ionary effects on cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

1973
1973
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 35 publications
1
14
0
2
Order By: Relevance
“…It is clear that, generally, the saturation level, N st , is close to the number of initial active sites on the surface. Hence, an apparent surface nucleation rate, I S , can be estimated by the following equation [12]:…”
Section: Diamond Paste-polished Surfacesmentioning
confidence: 99%
“…It is clear that, generally, the saturation level, N st , is close to the number of initial active sites on the surface. Hence, an apparent surface nucleation rate, I S , can be estimated by the following equation [12]:…”
Section: Diamond Paste-polished Surfacesmentioning
confidence: 99%
“…For instance, experimental data show that nuclei number density (n) of a new phase (crystals, droplets) depends simultaneously on both time (t) and supersaturation (Δμ), i.e., n = n(t, Δμ). S-shaped dependences of n vs. t at constant supersaturation have been known to cause electrochemical new-phase nucleation for a long time e.g., [13,14]. But they remained unelucidated [15] until recently, when it was shown that they obey logistic functional dependence [16].…”
Section: Resultsmentioning
confidence: 99%
“…Using digitalized original experimental data from [14,18], logistic dependences (with very high goodness of fit, R 2 ) are presented in Figures 1 and 2. Such time dependence has also been established for bovine β-lactoglobulin crystal nucleation which proceeds by a TSNM [6].…”
Section: Resultsmentioning
confidence: 99%
“…The so-called stochastic approach to crystal nucleation has been introduced for undercooled low viscous (mPa s) liquids, such as metals and hydrous suspensions (Toschev and Markov, 1967;Toschev and Gutzow, 1972;Toschev, 1973;Morton et al, 1994;Barlow and Haymet, 1995;Uttormark et al, 1997;Heneghan et al, 2001Wilson et al, 2005;Wilde et al, 2006Wilde et al, , 2009Yang et al, 2009Yang et al, , 2011Yang et al, , 2013. Our results show that it is applicable to high viscous (kPa s) silicate melts and it results in heterogeneous (HET) crystal nucleation rates from which TTT representations and critical cooling rates can be derived.…”
Section: Introductionmentioning
confidence: 87%
“…Already in the 1960s, Toschev and Markov (1967) showed that the electrolytic deposition of cadmium on platinum single crystal electrodes follows a Poisson distribution. Thereby, both the number of nuclei in a given time interval and the time necessary to form a certain number of nuclei are linked to probability distributions (Toschev and Gutzow, 1972;Toschev, 1973).…”
Section: Introductionmentioning
confidence: 99%